Kierkegaard's Fear and trembling : a reader's guide - Carlisle, Clare, 1977- (Continuum reader's guides., 2010)
Søren Kierkegaard was without question one of the most important and influential thinkers of the nineteenth century. Fear and Trembling is a classic text in the history of both philosophical and religious thought that still challenges readers with its original philosophical perspective and idiosyncratic literary style. Kierkegaard's 'Fear and Trembling': A Reader's Guide offers a concise and accessible introduction to this hugely important and notoriously demanding work. Written specifically to meet the needs of students coming to Kierkegaard for the first time, the book offers guidance on.